Cybaeus (Araneae: Cybaeidae) in the Nearctic: the devius and tardatus species groups of the Californian clade - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2021)
Species of North American Cybaeus L. Koch (Araneae: RTA clade: Cybaeidae) are moist-forest spiders classified in Holarctic and Californian clades. Here, in the fourth paper in a planned series reviewing the six Californian clade species groups, we review the species of the devius and tardatus groups. We recognize five species in the devius group (Cybaeus bilectus Bennett spec. nov., C. bryoncavus Bennett spec. nov., C. devius Chamberlin & Ivie, C. echo Bennett spec. nov., and C. wilsonia Bennett spec. nov.) and four in the tardatus group (C. orarius Bennett spec. nov., C. piazzai Bennett spec. nov., C. tardatus Chamberlin, and C. topanga Bennett spec. nov.). All of these species are rarely encountered and have restricted distributions either in the central and southern Sierra Nevada Mountains of eastern California, U.S.A (devius group) or the southern coast of western California (tardatus group). Some of these species are likely endangered or already extinct; most have not been seen in many decades and none have been collected more recently than 1995. Descriptions, illustrations, distribution maps, and identification keys are provided as well as a discussion of conservation issues of relevance to the group.